Aquisição de habilidades motoras de diferentes contextos com mesma demanda - Bruno Roberto Santos (2017)
Motor learning can be influenced by different factors, and knowledge of results (KR) is a kind of extrinsic feedback, one of these. The KR can be provided in different ways, but all seek to optimize the acquisition of motor skills process. Among these forms, the bandwidth KR stands out, which allows a margin of error, in which the performance determines the moment when the KR is provided by the researcher, teacher or instructor. It has been observed that the effects of the bandwidth KR in the acquisition of motor skills have presented inconclusive results when thinking about motor skills in a general way. However, an analysis that takes into account the context of these motor skills and their demand may provide a clearer understanding of the effect of this form of KR delivery. Thus, the objective of the present study was to verify the acquisition of motor skills of different contexts with the same demand, providing KR by the bandwidth. Being that independent of the context of the skill one expects not to find difference of the groups and also in the two tasks that present demand of control of the force. The study was composed of two experiments. The first had a sample composed of 48 volunteers of both sexes, from 18 to 35 years old and inexperienced in the task. The effect of the bandwidth KR was analyzed in two groups (with bandwidth KR and without bandwidth KR), in which the volunteers had to learn to control the palmar grip strength (dynamometer) considered from a context away from the real world. The second experiment with a task closer to the real world, with the same delineation of the first one, had a sample composed of 24 volunteers of both sexes, from 18 to 35 years old and that reached a criterion of entrance in the task. Inserted in a sporting context, culturally determined motor skills, volunteers had to make volleyball sneakers, controlling the force with the goal to achieve a goal. The results indicated that there was learning in both experiments and that there was no significant difference between the groups. Regardless of the context in which the task is inserted there was learning and the variable bandwidth KR resembled a 100% KR condition. These results can be explained by the quantitative and qualitative condition of the KR amplitude range, which makes the groups equal to the KR supply, both are 100%